Comparison of stereological correction procedures for liberation measurements - D. Lin; J. A. Finch (The Institute of Materials, Minerals and Mining, 1995)
The robustness of the large-sections correction procedure, Hill's fast approximation, Barbery's correction and the PARGEN correction was examined by comparing their ability to reconstruct the true liberation distribution using sectioning data from computer-generated spheres. The results indicate that the flexibility of a correction procedure is related to the assumptions it makes about the continuity of the liberation distribution, locked-particle characteristics and ore texture. Overall, the large-sections procedure appeared to be the most generally applicable. The Hill fast approximation performed well, but this was probably because it partially incorporates the sphere model; the performance of the PARGEN and Barbery corrections varied from case to case.